Exploring employee morale at the Port Elizabeth plant of Cadbury (South Africa) - Wolfaardt, Michelle (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
In the current business climate, performance is increasingly determined by how flexibly and effectively companies can utilize their human resources and this in tum, is influenced by employee morale. Morale refers to a state of psychosomatic health marked by an energetic, decisive resolution to achieve a given goal. When morale is low, employees may do what is required but do not have the energy to 'go the extra mile'. The importance of maintaining high morale is thus evident. The following project involved a study of morale in Cadbury's Port Elizabeth plant. Cadbury management was concerned about low morale following a recent merger with Bromor Foods. They thus wanted to assess: the state of current morale; any factors that may be influencing it; indicators of low morale (so that it may be monitored in the future) and finally, ways of addressing any existing morale issues. In order to achieve these aims, the researcher conducted interviews with various people to explore morale issues from employees' perspectives. She then sought confirmation for these views at the organizational level through the use of a survey. Statistical and thematic analyses showed morale to be low for middle managers and revealed a variety of indicators and influencing factors, as well as suggestions for addressing them. Despite the need to boost the sample size with convenience sampling, and thus, reduced representivity, the research was successful in answering the research aims.
Keywords: Cadbury Ltd; Chocolate industry -- South Africa -- Port Elizabeth; Employee morale; Job satisfaction; Performance standards; Employees -- Rating of; Personnel management